Its glory is in its age : grandeur et décadence dans l’expérience de l’environnement architectural victorien - Isabelle Cases (Cahiers Victoriens et Edouardiens)
Victorian architecture was marked by the construction of new types of industrial and commercial buildings which were sometimes presented as symbols of national power and progress. Yet in many cases those buildings rapidly became obsolete, as further industrial developments demanded bigger structures or imposed new conditions. As for workers, they most of the time had to live in poor-quality or prematurely dilapidated houses. On the other hand, eminent participants to the architectural debates of the period underlined the necessity to preserve monuments of the past and ancient buildings, and did not hesitate to praise « Old English » styles. Ageing in the Victorian architectural environment could therefore be synonymous with greatness or decline, sublimation or degradation, depending on the social and intellectual context.